O itinerário de duas uspianas na UFPB - Joana Neves e Rosa Maria Godoy Silveira: trajetórias que se cruzam a partir da História ensinada - Virgulino, Maria Helena Cavalcanti (2016)
Our work has as study object the recomposition of professional trajectories of two historians of the Department of History of UFPB: Joana Neves (1978-1985) and Rosa Maria Godoy Silveira (1976- 2003), with regard to the history of education, what took us to focus our research on the period in which they taught at UFPB, while glimpsing their performances and productions in this field until today, which made us extrapolate the established time frame, as they remain involved with the issues related to education of history. We started on the assumption that the trajectories of the teachers Joana Neves and Rosa Maria Godoy Silveira were marked by a constant concern for the teaching of history, this concept resulting a close relationship between teaching and research. Other teachers who worked with them in the Department of History of UFPB were influenced by their work, like many other professionals in their trajectories, graduates of this course, which now operate in various institutions of higher and basic education. Education combined with research, resulting in a conception of the first as production of knowledge; history professional’s developement as a teacher and researcher; thematic education; working conditions, among other concerns, provided the basis and underpin the design of history teaching advocated and practiced by these two teachers. In the restoration of their trajectories, we started from specific moments of their lives that influenced the choice of teaching and specifically the history line, and then we used as sources their statements and their intellectual productions, crossing on the trajectory of each, the defense of history taught.